To solve the linear-quadratic system using the elimination method, we have the following equations:
-
\( y = x^2 + 10 \) (quadratic equation)
-
\( y = -7x - 2 \) (linear equation)
To use the elimination method, we can set the two expressions for \( y \) equal to each other:
\[ x^2 + 10 = -7x - 2 \]
Now, let's rearrange the equation to set it to zero:
\[ x^2 + 7x + 12 = 0 \]
Now, we factor the quadratic:
\[ (x + 3)(x + 4) = 0 \]
Setting each factor equal to zero gives us the possible \( x \) values:
- \( x + 3 = 0 \) → \( x = -3 \)
- \( x + 4 = 0 \) → \( x = -4 \)
Next, we substitute these \( x \) values back into the linear equation to find the corresponding \( y \) values.
- For \( x = -3 \):
\[ y = -7(-3) - 2 = 21 - 2 = 19 \]
So, one solution is \( (-3, 19) \).
- For \( x = -4 \):
\[ y = -7(-4) - 2 = 28 - 2 = 26 \]
So, another solution is \( (-4, 26) \).
Thus, the solutions to the system are:
\[ (-3, 19) \quad \text{and} \quad (-4, 26) \]
The correct response is:
(−3,19) and (−4,26).